Fresh‐Frozen Bone Allografts in Maxillary Alveolar Augmentation: Analysis of Complications, Adverse Outcomes, and Implant Survival. Issue 11 (1st November 2016) - Deluiz, Daniel; Oliveira, Luciano; Fletcher, Paul; Pires, Fábio R.; Nunes, Marcus A.; Tinoco, Eduardo M.B.
Abstract : Background: Success of any bone augmentation procedure is dependent on several factors. Because complications occur in some cases, the aims of this study are to analyze adverse events associated with placement of fresh‐frozen bone allografts (FFBAs) during alveolar ridge augmentation and to assess 1‐year survival of dental implants placed in reconstructed sites. Methods: Fifty‐eight consecutive patients (15 males and 43 females, aged 38 to 76 years; mean age: 58 ± 9.2 years) requiring maxillary bone reconstruction prior to implant placement were enrolled in this study. A total of 268 implants was subsequently placed in sites reconstructed with FFBAs. There were 22 posterior grafted sites, 19 anterior, and 17 full‐arch sites. After a 4‐ to 6‐month integration period, all patients received an implant‐supported fixed prostheses. Complications occurring during treatment and the 12‐month follow‐up period were recorded and evaluated. Results: Thirteen of 58 (22.41%) patients experienced some kind of complication in the receptor site. Infection occurred in six (10.34%) individuals, dehiscence in five (8.62%), and mucosal perforation in seven (12.07%). Adverse outcomes categorized as partial and total graft loss occurred in four (6.90%) and three (5.17%) patients, respectively. Implant failure rate was 16 (5.97%) of the 268 fixtures placed in 12 (20.70%) of 58 patients. Conclusions: Infection and suture dehiscence are significantly correlated with graft loss in a maxillary FFBA augmentation. Patients with full‐arch grafting reconstructions lost significantly more implants. Early diagnosis and prompt management of adverse events seem to be of great importance in prevention of total graft loss.